Tunjangan Kinerja Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Sidoarjo - Nia Rifatul Izza; Muslimin Muslimin (Journal of Management and Bussines (JOMB), 2024)
This research aims to evaluate and test the impact of performance allowances, work motivation and work discipline on employee performance at the Regional Financial and Asset Management Agency of Sidoarjo Regency. The research method used is quantitative by collecting primary data through quantitative surveys. The research results show that performance allowances, work discipline and work motivation together influence employee performance by 52.5%, while the remaining 47.5% is influenced by other factors outside the variables studied. The F test also shows that the independent variables, namely performance allowances, work discipline, and work motivation, significantly influence employee performance together. This indicates that changes in performance allowances, work discipline, and work motivation will have an impact on changes in employee performance. These findings confirm that performance benefits, work discipline, and work motivation have a significant influence on employee performance. The conclusion is that increasing performance allowances, monitoring and improving work discipline, as well as increasing work motivation can improve employee performance at the Regional Financial and Asset Management Agency of Sidoarjo Regency. Keywords: Discipline, Performance, Benefits